Aerospace technology, a global dizzying advance, its applications and problems in Agricultural Sciences - Yánez-Cajo, Danilo (2021)
Aerospace technology in the last ten years has been developing rapidly, its applications are found in most lines of knowledge. Specifically, in agricultural sciences its use has increased due to two great factors. The first is the support to generate solutions to many of the problems of optimization and crop yield, within an era of exponential population growth, which has increased the need to improve food yield based on technologies, in a globalized world. whose social reproduction is based on the accumulation of capital. The second point is the development of electronic, mechanical and physical engineering, which, based on the mentioned social and agricultural needs, is innovated and developed aerospace technology that provides solutions to these problems. In this context, we bring out the benefits of aerospace technology in agricultural sciences, citing studies by various authors who have applied this technology, but at the same time we will also address the indirect negative consequences that its use in the agricultural process can cause, in space in the replacement of work and human labor, in addition to the limitation of access of this technology to small agricultural groups, and its future in the globalized world.